Macro-Economic Determinants Sharia Share Prices - Rahmat Daim Harahap; Fitriani Saragih; Sugianto Sugianto; Iskandar Muda (Lembaga Riset Ilmiah, 2022)
The capital market is an indicator of a country's economic progress in supporting the economy of the country concerned. The purpose of this study is to analyze the macroeconomic determinants of Islamic stock prices. The research method uses a quantitative approach to secondary data in time series with the Vector Error Correction Model (VECM) and uses the help of the eviews 9 programs. This study uses monthly data from 2017 to 2021. The results of this study indicate that in the long term the variables of GDP and INFLATION hurts ISSI, while the JUB and KURS variables have a positive and significant effect on ISSI. In the short term, the variables of GDP, INFLATION, JUB, and EXCHANGE have no effect on ISSI